Serum amyloid P: a systemic regulator of the innate immune response. Issue 5 (7th May 2014) - Cox, Nehemiah; Pilling, Darrell; Gomer, Richard H.
Abstract : Review on SAP affects neutrophil adhesion, monocyte differentiation, and macrophage polarization in the innate immune system. Abstract : The pentraxin SAP reduces neutrophil adhesion to ECM proteins, inhibits the differentiation of monocytes into fibrocytes, attenuates profibrotic macrophages, activates the complement pathway, and promotes phagocytosis of cell debris. Together, these effects of SAP regulate key aspects of inflammation and set a threshold for immune cell activation. Here, we present a review of SAP biology with an emphasis on SAP receptor interactions and how the effect of SAP on monocytes and macrophages has been explored to develop this protein as a therapeutic for renal and lung injuries. We also discuss how there remain many unanswered questions about the role of SAP in innate immunity.